An instructional approach in mathematics learning for fourth-grade students based on collaborative learning and inquiry-based learning - Yu, Siliang; Jantharajit, Nirat; Srikhao, Sarit (Asian Journal of Contemporary Education, 2024)
This study combines collaborative learning and inquiry-based learning, analyzes the characteristics of fourth-grade mathematics textbook, and designs a instructional model based on collaborative learning and inquiry-based learning. Based on this instrcutional model, this study adopts a quasi-experimental design, involving 142 fourth-grade students from a public primary school in Chengdu, China, using pre-tests and post-tests to measure the effectiveness of the instrcutional model. The main research results indicate that students who receive instrcutional approach based on collaborative learning and inquiry-based learning show significant improvement in analytical thinking and reasoning skills compared to students receiving traditional teaching approach. The main contribution of this study lies in demonstrating that instrcutional approach based on collaborative learning and inquiry-based learning can effectively enhance the mathematical analytical thinking and reasoning skills of fourth-grade students, providing a replicable framework for educational practice.